Low-melting-point composite lithium salt, preparation method thereof and lithium ion battery positive electrode material
Through the preparation method of low-melting point composite lithium salt, the problems of reaction unevenness and the complexity of traditional molten salt methods in the synthesis of lithium-ion battery positive electrode materials are solved, and the performance of lithium-ion battery positive electrode materials and the adaptability of industrial production are achieved.
Patent Information
- Application Number
- CN202510011164.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-22
AI Technical Summary
In the existing synthesis methods of lithium-ion battery positive electrode materials, the uniformity of the solid phase reaction is affected by the particle size of the precursor and lithium source, resulting in uneven lithiation process and poor product performance consistency. The traditional molten salt method introduces unnecessary elements, which makes the synthesis path complex and low efficiency, making it not suitable for industrial production.
The preparation method of low-melting point composite lithium salt is prepared by mixing ingredients, forming rods, melting treatment and aerosol powder making steps, and is prepared as the lithium source of the positive electrode material of lithium-ion batteries, and mixed with the nickel-cobalt-manganese precursor to form a uniform positive electrode material.
By providing a liquid environment, it promotes the uniform reaction between lithium ions and precursors, improves the electrochemical performance and cycle life of the cathode material, and the preparation method is efficient, fast and low-cost, suitable for industrial batch preparation.
Smart Images

Figure CN119858943A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery positive electrode materials, and in particular to a low melting point composite lithium salt and a preparation method thereof, and a lithium ion battery positive electrode material. Background Art
[0002] The positive electrode material of lithium-ion batteries is a crucial component of lithium-ion batteries. It not only affects the performance of the battery, but also directly affects the cost and safety of the battery. The main types of positive electrode materials on the current market are lithium nickel cobalt manganese oxide and lithium iron phosphate. Lithium-rich manganese-based positive electrode materials have become the next generation of positive electrode materials that have attracted much attention due to their high capacity and low cost. The synthesis methods of lithium-ion positive electrode materials include solid-phase sintering method, sol-gel method, hydrothermal method, etc. The solid-phase method is the most widely used method in industry. Specifically, the lithium salt and the precursor are evenly mixed and then calcined at high temperature, and the positive electrode material is obtained through solid-phase reaction and crystal growth. However, the solid-phase reaction needs to go through a slow diffusion process, and the uniformity of the reaction is affected by the particle size of the precursor and the lithium source. In particular, if the particles of the lithium source are too large, the lithiation process of the positive electrode material will be uneven, resulting in poor consistency in the performance of its product. Using crushing to reduce its particle size can effectively improve the problem of reaction inhomogeneity. The smaller the particles, the better the reaction uniformity, but crushing will increase the material cost. The smaller the particles, the greater the material cost, and it is difficult to balance the contradiction.
[0003] The molten salt method is a commonly used method for synthesizing ceramics. Using low-melting point compounds (such as lithium chloride-potassium chloride, sodium chloride-sodium sulfate, etc.) as solvents, placing the solid-phase reaction in a liquid phase system can greatly improve its reaction uniformity and improve material performance. For example, patent CN 116143200 A discloses a high-pressure compacted micron single crystal lithium-rich manganese-based positive electrode material and a preparation method. During the first calcination, additional molten salt is added to optimize the morphology of the single crystal particles. However, traditional molten salts often introduce unnecessary other elements and require subsequent filtration and washing. The synthesis path is complex and the efficiency is low, which is not suitable for industrial production. Studies have shown that compared with the traditional single lithium source, two or more lithium salts will also form a low eutectic salt, which can also improve its electrochemical performance when used as a lithium source for synthesizing positive electrode materials. For example, patent CN 113707873 A discloses a battery positive electrode material using a low-melting-point lithium salt and a preparation method thereof. A low-melting-point lithium salt is prepared by selecting a lithium salt with a suitable melting point and activity. The low-melting-point lithium salt is used as a lithium element donor and then mixed with a nickel-cobalt-manganese precursor and then calcined once. This effectively improves the mixing uniformity of the lithium salt and the precursor during the calcination process, improves the normal and high-temperature cycle performance of the material, and has the advantages of low calcination temperature, low energy consumption and good electrochemical performance. However, the uniformity of the low-melting-point lithium salt prepared in this patent is limited by the particle size of each lithium salt, and it is difficult to achieve molecular-level uniformity, and the effect needs to be further improved. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a low melting point composite lithium salt.
[0005] The second object of the present invention is to provide a low melting point composite lithium salt prepared by the preparation method.
[0006] The third object of the present invention is to provide a lithium-ion battery positive electrode material prepared from the low-melting point composite lithium salt.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a method for preparing a low melting point composite lithium salt, comprising the following steps:
[0009] (1) mixing the following raw materials in percentage by mass: 11-89% of a first lithium source, 11-89% of a second lithium source, and 0-10% of a dopant to obtain a composite lithium salt powder;
[0010] The first lithium source is lithium carbonate; the second lithium source is at least one selected from lithium hydroxide monohydrate, lithium nitrate, lithium chloride, lithium sulfate, lithium acetate, and lithium oxalate;
[0011] The dopant is selected from one or more of the following compounds:
[0012] Alkali metal salts, their oxides or hydroxides;
[0013] Salts of alkaline earth metals, their oxides or hydroxides;
[0014] Salts, oxides or hydroxides of elements of groups IIIA to VA;
[0015] Salts of transition metals, their oxides or hydroxides;
[0016] Salts of rare earth metals, their oxides or hydroxides;
[0017] (2) Rod forming: forming the composite lithium salt powder to obtain a molded body;
[0018] (3) Melting the material: The molded body is melted to obtain a melt;
[0019] (4) Gas atomization powder making: The melt is atomized and broken into fine droplets through a nozzle, and becomes powder after cooling;
[0020] (5) Powder collection and screening: The powder obtained by atomization is screened to obtain a low melting point composite lithium salt.
[0021] Step (1):
[0022] The first lithium source (lithium carbonate) accounts for 11 to 89 wt % of the total raw materials; preferably 30 to 79 wt %; more preferably 35 to 40 wt %.
[0023] The second lithium source (lithium hydroxide and / or other lithium salts) accounts for 11 to 89 wt % of the total raw materials; preferably 21 to 70 wt %; more preferably 60 to 65 wt %.
[0024] The salt of the alkali metal, its oxide or hydroxide may be sodium hydroxide, sodium salt (including but not limited to sodium carbonate, sodium sulfate, sodium chloride, sodium acetate, sodium oxalate), potassium hydroxide, potassium salt (including but not limited to potassium carbonate, potassium sulfate, potassium chloride, potassium acetate, potassium oxalate), etc.;
[0025] The salt of the alkaline earth metal, its oxide or hydroxide may be magnesium hydroxide, a magnesium salt (including but not limited to magnesium carbonate, magnesium sulfate, magnesium chloride, magnesium acetate, magnesium oxalate), etc.;
[0026] The salt of the IIIA to VA main group element, its oxide or hydroxide may be one or more of the salts or oxides of B, Al, Sn, Sb.
[0027] The salt, oxide or hydroxide of the transition metal may be one or more of the salts of Ti, Cr, Fe, Zn, Y, Zr, Nb, Mo, W or their oxides.
[0028] The salt, oxide or hydroxide of the rare earth metal may be one or more of the salts or oxides of La and Ce.
[0029] The dopant accounts for 0 to 10 wt % of the total raw materials; preferably 0 to 5 wt %, and more preferably 0.5 to 3 wt %.
[0030] Step (1) specifically comprises: weighing several raw materials according to a predetermined ratio, and mixing them evenly in a mixer to obtain a composite lithium salt powder.
[0031] Step (2):
[0032] In some embodiments, step (2) comprises: placing the composite lithium salt powder into a rubber sheath and forming a rod-shaped body on a cold isostatic press.
[0033] Step (3):
[0034] Melting materials: The melting process is carried out in the smelting device supporting the gas atomization equipment. The heating method adopts electric furnace heating. The powder molding is heated to 450-700℃ in a graphite crucible to melt it into liquid. It is kept for 10-30 minutes to make it uniform. The melting device is sealed and filled with nitrogen as a protective gas. The gas pressure is kept at a slightly positive pressure.
[0035] Step (4):
[0036] The gas atomization method is to use high-speed airflow to impact the molten metal, convert the kinetic energy of the gas into the surface energy of the molten metal through collision, so that the molten metal flow is broken into fine droplets, which are then quickly cooled and solidified in the airflow atmosphere to form powder.
[0037] Gas atomization powder making: The melt is sent from the smelting device into the atomization tank of the gas atomization equipment. Under nitrogen protection, the melt is atomized and broken into fine droplets through the nozzle at a gas pressure of 1.0 to 5.5 MPa. The droplets are quickly cooled and solidified in the high-speed airflow to become powder.
[0038] Step (5):
[0039] Powder collection and screening: The powder obtained by aerosolization is screened through a 200-mesh sieve to obtain suitable powder. The coarse powder on the sieve can be repeated in step (2) and subsequent aerosolization powder making and recycled.
[0040] In a second aspect, the present invention provides a low melting point composite lithium salt prepared by the above preparation method.
[0041] In a third aspect, the present invention provides a positive electrode material for a lithium-ion battery, which is obtained by mixing and calcining the above-mentioned low-melting-point composite lithium salt and a positive electrode material precursor for a lithium-ion battery.
[0042] Lithium-ion battery positive electrode material precursors include but are not limited to nickel-cobalt-manganese precursors and the like.
[0043] Technical effects:
[0044] (1) The present invention discloses a low melting point composite lithium salt. Combining the eutectic theory and systematic experiments, the optimal ratio of each lithium salt is optimized. When used as a lithium source, a liquid environment is provided to promote a more uniform solid phase reaction with a precursor, thereby improving the performance of the positive electrode material of a lithium ion battery.
[0045] (2) The present invention uses a composite lithium salt containing a certain amount of alkali metal or alkaline earth metal, which can achieve ion doping when reacting with the positive electrode precursor. The liquid environment provided by the composite lithium salt makes the doping more uniform, stabilizes the crystal structure of the material, and improves the cycle life.
[0046] (3) The present invention prepares low-melting-point composite lithium salts through the melting-atomization method, which can fully mix different lithium salts and doping raw materials to achieve molecular-level uniformity, which is more conducive to the solid-phase reaction during the sintering process after lithium addition, thereby obtaining a positive electrode material with a more uniform structure and better performance.
[0047] (4) The composite lithium salt powder is prepared by the technology of the present invention, which has the advantages of high efficiency, rapidity and low cost, and is suitable for industrial batch preparation.
[0048] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The DSC curve of the low melting point composite lithium salt of Example 1;
[0050] Figure 2 The DSC curve of the low melting point composite lithium salt of Example 2;
[0051] Figure 3 The DSC curve of the low melting point composite lithium salt of Example 3;
[0052] Figure 4 The charge and discharge curve of a button cell assembled with the positive electrode material prepared using the low melting point composite lithium salt of Example 1 and the lithium carbonate of Comparative Example 1 as the lithium salt;
[0053] Figure 5 The figure is a rate cycle curve of a button cell assembled with a positive electrode material prepared using the low melting point composite lithium salt of Example 1 and the lithium carbonate of Comparative Example 1 as lithium salt. DETAILED DESCRIPTION
[0054] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0055] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0056] Example 1
[0057] 1) Batching and mixing: Weigh 2446 g of Li2CO3, 3954 g of LiOH·H2O and 64 g of NaOH, and mix the three raw materials evenly in a mixer;
[0058] 2) Rod forming: put the powder mixed in the previous step into the rubber sleeve and make a rod-shaped material on a cold isostatic press;
[0059] 3) Melting materials: Put the rods in the previous step into a smelting device equipped with a gas atomization device, use a graphite crucible, and heat the powder molded body in the graphite crucible to melt the rods. The melt temperature reaches 500° C., and the melt is kept warm and stirred for 30 minutes to make it uniform. The smelting device is kept sealed and filled with nitrogen during the treatment process, and the pressure in the smelting device is kept at 0.101 MPa;
[0060] 4) Gas atomization powder making: The melted liquid in the previous step is transported to the atomization tank of the gas atomization equipment at a pressure of 0.101MPa and a constant temperature of 500℃. The liquid is atomized and broken into fine droplets through the nozzle at a gas pressure of 3.5MPa. The droplets are quickly cooled and solidified in the high-speed airflow to become powder.
[0061] 5) Powder collection and sieving: The powder obtained by atomization is sieved through a 200-mesh sieve to obtain a suitable powder. The powder is subjected to DSC test in a nitrogen atmosphere, and the curve is as follows: Figure 1 As shown, an obvious peak appears at about 425°C, which is the melting point of the powder.
[0062] Example 2
[0063] Weigh 2445 g of Li2CO3, 3797 g of LiOH·H2O, 264 g of LiNO3, and 65 g of NaOH and mix the four raw material powders evenly in a mixer.
[0064] The remaining steps are the same as those in Example 1. The powder is subjected to DSC test in a nitrogen atmosphere, and the curve is as follows: Figure 2 As shown, an obvious peak appears at about 418°C, which is the melting point of the powder.
[0065] Example 3
[0066] Weigh 2352 g of Li2CO3, 3542 g of LiOH·H2O, 422 g of LiNO3, and 63 g of NaOH, and mix the four raw materials evenly in a mixer.
[0067] The remaining steps are the same as those in Example 1. The powder is subjected to DSC test in a nitrogen atmosphere, and the curve is as follows: Figure 3 As shown, an obvious peak appears at about 411°C, which is the melting point of the powder.
[0068] Example 4
[0069] Weigh 2712 g of Li2CO3, 2102 g of LiOH·H2O, 797 g of LiNO3, and 56 g of NaOH, and mix the four raw materials evenly in a mixer.
[0070] The remaining steps are the same as those in Example 1.
[0071] Example 5
[0072] Weigh 2446 g of Li2CO3 and 3954 g of LiOH·H2O as lithium sources, and 64 g of Mg(OH)2, and mix the three raw materials evenly in a mixer.
[0073] The remaining steps are the same as in Example 1.
[0074] Example 6
[0075] Weigh 2446 g of Li2CO3 and 3954 g of LiOH·H2O as lithium sources, and 128 g of Mg(OH)2, and mix the three raw materials evenly in a mixer.
[0076] The remaining steps are the same as in Example 1.
[0077] Example 7
[0078] Weigh 2712 g of Li2CO3, 2102 g of LiOH·H2O, 797 g of LiNO3, and 56 g of Mg(OH)2, and mix the four raw materials evenly in a mixer.
[0079] The remaining steps are the same as in Example 1.
[0080] Comparative Example 1
[0081] As the lithium salt, commercially available lithium carbonate was used.
[0082] Comparative Example 2
[0083] Weigh 2446 grams of lithium carbonate and 3954 grams of lithium hydroxide monohydrate, and mix these two lithium-containing raw materials evenly in a mixer.
[0084] Comparative Example 3
[0085] Weigh 2446 grams of lithium carbonate, 3954 grams of lithium hydroxide monohydrate and 64 grams of sodium hydroxide, and mix the three raw materials evenly in a mixer.
[0086] Test example:
[0087] According to the methods of the examples and comparative examples, lithium salt and other additives were prepared; lithium salt and Ni 0.4 Co 0.2 Mn 0.4 The (OH)2 precursor was mixed in a 1.05:1 lithium ratio, calcined at 900°C for 15 hours, cooled to room temperature, crushed and sieved to obtain a lithium-rich manganese-based positive electrode material;
[0088] Assemble the button cell battery:
[0089] The prepared lithium-rich manganese-based material was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the polypropylene microporous membrane was used as the separator, and LiPF6 / EC+DMC was used as the electrolyte. A button cell was assembled and the electrochemical performance was tested. The results are shown in Table 1.
[0090] Table 1
[0091]
[0092] The first charge and discharge curves of the buckle prepared by lithium salt in Example 1 and Comparative Example 1 are as follows: Figure 4 The results show that the first discharge specific capacity and coulombic efficiency of the samples prepared by the method of the present invention are significantly better than those of the samples of the comparative example using lithium carbonate as the lithium salt. Figure 5 As shown, the rate performance is also significantly better than the control sample.
[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a low melting point composite lithium salt, characterized in that: The following steps are involved: (1) mixing the following raw materials in percentage by mass: 11-89% of a first lithium source, 11-89% of a second lithium source, and 0-10% of a dopant to obtain a composite lithium salt powder; The first lithium source is lithium carbonate; the second lithium source is at least one selected from lithium hydroxide monohydrate, lithium nitrate, lithium chloride, lithium sulfate, lithium acetate, and lithium oxalate; The dopant is selected from one or more of the following compounds: Alkali metal salts, their oxides or hydroxides; Salts of alkaline earth metals, their oxides or hydroxides; Salts, oxides or hydroxides of elements of groups IIIA to VA; Salts of transition metals, their oxides or hydroxides; Salts of rare earth metals, their oxides or hydroxides; (2) Rod forming: forming the composite lithium salt powder to obtain a molded body; (3) Melting the material: The molded body is melted to obtain a melt; (4) Gas atomization powder making: The melt is atomized and broken into fine droplets through a nozzle, and becomes powder after cooling; (5) Powder collection and screening: The powder obtained by atomization is screened to obtain a low melting point composite lithium salt.
2. The preparation method according to claim 1, characterized in that: The alkali metal or alkaline earth metal salt or hydroxide of step (1) is at least one selected from sodium hydroxide, sodium salt, potassium hydroxide, potassium salt, magnesium hydroxide, and magnesium salt; The salt, oxide or hydroxide of the IIIA to VA main group element is one or more salts or oxides thereof selected from B, Al, Sn, Sb; The transition metal salt, oxide or hydroxide thereof is one or more selected from the group consisting of Ti, Cr, Fe, Zn, Y, Zr, Nb, Mo, W salts or oxides thereof; The salt, oxide or hydroxide of the rare earth metal is one or more selected from the salts or oxides of La and Ce.
3. The preparation method according to claim 1, characterized in that: Step (1) comprises: weighing the raw materials according to a predetermined ratio, and mixing them evenly in a mixer to obtain a composite lithium salt powder.
4. The preparation method according to claim 1, characterized in that: Step (2) comprises: putting the composite lithium salt powder into a rubber sheath and forming a rod-shaped body on a cold isostatic press.
5. The preparation method according to claim 1, characterized in that: Step (3) Melting is carried out by heating in an electric furnace. The molded body is heated to a temperature of 450-700° C. in a graphite crucible to melt it into a liquid. The temperature is maintained for 10-30 minutes to make it uniform. The molded body is sealed and filled with nitrogen as a protective gas. The gas pressure is maintained at a slightly positive pressure.
6. The preparation method according to claim 1, characterized in that: In step (4), the melt is atomized and broken into fine droplets through a nozzle at a gas pressure of 1.0 to 5.5 MPa. The droplets are rapidly cooled and solidified in a high-speed airflow to become powder.
7. The preparation method according to claim 1, characterized in that: Step (5) comprises: sieving the powder obtained by aerosolization through a 200-mesh sieve to obtain a suitable powder, and re-performing step (2) and subsequent steps with the coarse powder on the sieve for recycling.
8. A low melting point composite lithium salt, characterized in that: The low melting point composite lithium salt is prepared by the preparation method according to any one of claims 1 to 7.
9. A positive electrode material for a lithium ion battery, characterized in that: The low melting point composite lithium salt according to claim 8 is mixed and calcined with a precursor of a positive electrode material for a lithium ion battery.
10. The positive electrode material for lithium-ion batteries according to claim 9, characterized in that: The lithium-ion battery positive electrode material precursor is a nickel-cobalt-manganese precursor.
Citation Information
Patent Citations
High-compaction micron single crystal lithium-rich manganese-based positive electrode material, preparation method and lithium battery
CN116143200A
Cited By
Method for preparing lithium-rich manganese-based positive electrode material based on low-temperature sintering of composite lithium molten salt
CN122494539A